Progressive Proximal Spinal And Bulbar Musclar Atrophy Of Late Onset - Alagoury, - Malak Mohammed Saad (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Progressive spinal muscular atrophy, juvenile proximal spinal muscular atrophy "Kugelberg-Welander", and infantile muscular atrophy "Werdnig-Hoffman" comprise a group of diseases by virtue of their pathological similarity. Chronic degeneration of the lower motor neurons and neurogenic atrophy of the skeletal muscle are common to all. The diseases differ in mode of inheritance, age of onset, distribution of muscular atrophy, and prognosis. Some investigators have considered them as a continuum of the same disease, underscoring the pathological similarity, while others have emphasized the clinical differences and prefer to regard them as distinct entities. In describes 2 families in which 11 members, all male, were affected by an unusual, slowly progressive spinal and bulbar muscular atrophy. This disease, apparently inherited as a sex-linked recessive trait, becomes manifest clinically in the fourth and fifth decades and initially involves proximal muscles.The proximal weakness gave a clinical picture similar to muscular dystrophy in some patients. A full description is made of the prepositus of each family, but only the more striking features or unusual aspects in other cases
Progressive spinal muscular atrophy, juvenile proximal spinal muscular atrophy "Kugelberg-Welander", and infantile muscular atrophy "Werdnig-Hoffman" comprise a group of diseases by virtue of their pathological similarity. Chronic degeneration of the lower motor neurons and neurogenic atrophy of the skeletal muscle are common to all. The diseases differ in mode of inheritance, age of onset, distribution of muscular atrophy, and prognosis. Some investigators have considered them as a continuum of the same disease, underscoring the pathological similarity, while others have emphasized the clinical differences and prefer to regard them as distinct entities. In describes 2 families in which 11 members, all male, were affected by an unusual, slowly progressive spinal and bulbar muscular atrophy. This disease, apparently inherited as a sex-linked recessive trait, becomes manifest clinically in the fourth and fifth decades and initially involves proximal muscles.The proximal weakness gave a clinical picture similar to muscular dystrophy in some patients. A full description is made of the prepositus of each family, but only the more striking features or unusual aspects in other cases